2006
DOI: 10.1140/epjd/e2006-00166-3
|View full text |Cite
|
Sign up to set email alerts
|

Anderson localization of elementary excitations in a one-dimensional Bose-Einstein condensate

Abstract: Abstract. We study the elementary excitations of a transversely confined Bose-Einstein condensate in presence of a weak axial random potential. We determine the localization length (i) in the hydrodynamical low energy regime, for a domain of linear densities ranging from the Tonks-Girardeau to the transverse Thomas-Fermi regime, in the case of a white noise potential and (ii) for all the range of energies, in the "one-dimensional mean field regime", in the case where the randomness is induced by a series of ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
85
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(97 citation statements)
references
References 38 publications
10
85
1
1
Order By: Relevance
“…The properties of the elementary Bogoliubov excitations stemming from the Gross-Pitaevskii state were studied analytically in the superfluid regime. Their localization length was shown to exhibit a power law behavior as a function of energy: E α , with α = 2 deep in the superfluid phase [13] and α = 1 at the phase transition [14]. Numerically we found that α < 1 in the Bose glass phase [15].…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…The properties of the elementary Bogoliubov excitations stemming from the Gross-Pitaevskii state were studied analytically in the superfluid regime. Their localization length was shown to exhibit a power law behavior as a function of energy: E α , with α = 2 deep in the superfluid phase [13] and α = 1 at the phase transition [14]. Numerically we found that α < 1 in the Bose glass phase [15].…”
Section: Introductionmentioning
confidence: 65%
“…Thanks to the weak interaction limit, the theoretical description of these experiments can be performed in a first approximation with the Gross-Pitaevskii equation. The Gross-Pitaevskii equation in the presence of a disorder potential was recently studied by several groups [11][12][13][14]. For the condensate wave function, two different cases were identified: a connected density profile at weak and a fragmented one at strong disorder.…”
Section: Introductionmentioning
confidence: 99%
“…[495]). Another possibility is Anderson localization of elementary excitations in interacting BECs, as analyzed in the recent works [496,497]. Finally, it is worth also mentioning in passing parallel developments in this area, within the mathematically similar setting of photonic lattices, where Anderson localization and transition from ballistic to diffusive transport were recently observed in the presence of random fluctuations [498].…”
Section: Matter-waves In Disordered Potentialsmentioning
confidence: 89%
“…A central aim in this context is the realization and unambiguous identification of strong Anderson localization with Bose-Einstein condensates, which was attempted by several experimental groups [1][2][3] with recent success [4,5], and theoretically studied both from the perspective of the expansion process of the condensate [6,7] as well as from the scattering perspective [8,9]. Complementary studies were focused on localization properties of Bogoliubov quasiparticles [10,11], on dipole oscillations in the presence of disorder [12,13], as well as on the realization of Bose glass phases [14,15].The above-mentioned topics (apart from Ref.[7]) mainly refer to processes that are essentially one dimensional (1D) by nature. Qualitatively new phenomena, however, do arise in two or three spatial dimensions, due to the scenario of weak localization.…”
mentioning
confidence: 99%
“…The past years have witnessed an increasing number of theoretical and experimental research activities on the behavior of ultracold atoms in magnetic or optical disorder potentials [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. A central aim in this context is the realization and unambiguous identification of strong Anderson localization with Bose-Einstein condensates, which was attempted by several experimental groups [1][2][3] with recent success [4,5], and theoretically studied both from the perspective of the expansion process of the condensate [6,7] as well as from the scattering perspective [8,9].…”
mentioning
confidence: 99%